Comparison of the outcomes between laparoscopic radical prostatectomy and robotic-assisted laparoscopic radical prostatectomy: A 4-year single and high volume center experience - K. Weerapolchai (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND| 2019. Background: Prostate cancer is one of the most common cancers in men. The standard surgical approaches in localized prostate cancer are open, laparoscopic and robotic-assisted laparoscopic radical prostatectomy (RARP). Recently, RARP has been introduced as an alternative approach to standard laparoscopic radical prostatectomy (LRP). In the present study, we aimed to compare the outcomes between LRP and RARP during a 4-year period in Ramathibodi Hospital. Objective: Compare the outcomes between LRP and RARP during a 4-year period in Ramathibodi Hospital. Materials and Methods: The study was a retrospective observational study. We included patients with localized and locally advanced prostate cancer (stage T1-T3) receiving LRP or RARP in Ramathibodi Hospital during January 2013 and October 2016. Demographic data, baseline laboratory data, tumor staging and perioperative parameters were obtained from electronic medical records. The primary outcome was the comparison of free surgical margin and functional outcomes including incontinence rates and erectile dysfunction between LRP and RARP. The secondary outcomes were differences in perioperative parameters. Results: Two-hundred and forty-five patients were included; 103 in the LRP group and 142 in the RARP group. Baseline characteristics were similar between two groups, except higher pathological stage 3 and prostate volume in the RARP group. The rate of free surgical margins was 56.3% in LRP group vs. 63.3% in RARP group (p = 0.24). The rate of the patients who had incontinence was 19.4% in LRP vs. 30.3% in RARP (p = 0.48) and erectile dysfunction was 21.4% in LRP vs. 28.9% in RARP (p = 0.12). The operative time was similar in both groups. Biochemical recurrence and other perioperative parameters did not differ between the two groups. Conclusion: LRP and RARP provide similar outcomes in terms of oncological and functional results in a 4-year experience of our center. RARP may provide the better results in margin status compared to LRP. We encourage urologists in our Asian community to perform randomized studies to confirm these outcomes.